On Existence of Local Solutions of a Moving Boundary Problem Modelling Chemotaxis in 1-D (Journal of Partial Differential Equations, 2014)
" we prove the local existence and uniqueness of a moving boundary problem modeling chemotactic phenomena. We also get the explicit representative for the moving boundary in a special case."
Keywords: Keller-Segel model of chemotaxis; moving boundary; local existence; special case